The obligation to succeed when it matters the most–The influence of skill and pressure on the success in football penalty kicks. (March 2023) - Brinkschulte, Michel; Wunderlich, Fabian; Furley, Philip; Memmert, Daniel
Abstract: In order to gain a more comprehensive understanding of the influence of skill and pressure on the success in football penalty kicks, we analyzed 1711 penalties taken over a 15-year period in major international tournaments. We conducted a multiple correspondence analysis in order to reduce six variables that are associated with skill and pressure to two dimensions that reflect our target concepts. Then, we used these two factors as independent variables in a logistic regression and fit different models using three binary dependent variables. The results show that high situational pressure significantly increases the probability of missing the goal entirely by about 6%, independent of the player's skill level. The probability that the goalkeeper saves a penalty significantly decreases by roughly 4% when a highly skilled player takes the shot. In general, high situational pressure decreases the probability of scoring a penalty kick. Furthermore, the probability to score a penalty increases if a highly skilled player takes the kick which indicates that a high skill level can act as a kind of buffer against debilitating effects caused by performance pressure. Highlights: Use of MCA to statistically reduce multi-dimensional data to fewer factors. High pressure increases the chance that the penalty kick will miss the goal entirely. Goalkeeper success decreases when the penalty is taken by a highly skilled player.